2020
DOI: 10.14746/ssllt.2020.10.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frequency and idiomaticity on second language reading comprehension in children with English as an additional language

Abstract: Vocabulary plays an important role in reading comprehension in both the L1 and the L2 (Murphy, 2018). In measuring vocabulary knowledge, however, researchers typically focus on mono-lexical units where vocabulary assessments tend not to take into account multi-word expressions which include phrasal verbs, collocations, and idioms. Omitting these multi-word lexical items can lead to an over-estimation of comprehension skills, particularly in reading. Indeed, adult learners of English comprehend texts containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The finding highlights the importance of looking at vocabulary beyond single words to understand how vocabulary items are learned and processed in the company of other words. Previous research has already noted the importance of including multi-word vocabulary in the investigation of EAL comprehension research (Kan, 2014;McKendry, 2014;McKendry & Murphy, 2011;Smith & Murphy, 2015). The current study adds to this literature by highlighting the differential development of metaphor comprehension across tasks.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The finding highlights the importance of looking at vocabulary beyond single words to understand how vocabulary items are learned and processed in the company of other words. Previous research has already noted the importance of including multi-word vocabulary in the investigation of EAL comprehension research (Kan, 2014;McKendry, 2014;McKendry & Murphy, 2011;Smith & Murphy, 2015). The current study adds to this literature by highlighting the differential development of metaphor comprehension across tasks.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, the conventionality of phrases matters particularly for learners of EAL. Kan (2014) and Martinez and Murphy (2011) demonstrated that even highly frequent multiword phrases can cause unnoticed comprehension difficulties in learners of EAL and L2 learners, respectively. Collectively, these studies outline a critical role of frequency or conventionality of a phrase for how it is processed.…”
Section: Developing Metaphor Comprehensionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study also found that these students are unaware that their poor performance in comprehension is due to their lack of knowledge of collocations. Similarly, Kan and Murphy (2020) found that L2 students struggle to understand texts containing collocations and are unaware of their limitations in comprehension. Other studies in the field have also found that adult English learners have a harder time understanding texts with a higher number of collocations, even if the texts use the same words, compared to texts with fewer collocations (Martinez and Murphy, 2011).…”
Section: Figure 1 the Meaning And Phrase Changeability Across Colloca...mentioning
confidence: 98%